Chromatin accessibility illuminates single-cell regulatory dynamics of rice root tips - Feng, Dan; Liang, Zhe; Wang, Yifan; Yao, Jiaying; Yuan, Zan; Hu, Guihua; Qu, Ruihong; Xie, Shang; Li, Dongwei; Yang, Liwen; Zhao, Xin’Ai; Ma, Yanfei; et al. (BMC biology, 2022)
Root development and function have central roles in plant adaptation to the environment. The modification of root traits has additionally been a major driver of crop performance since the green revolution; however, the molecular underpinnings and the regulatory programmes defining root development and response to environmental stress remain largely unknown. Single-cell reconstruction of gene regulatory programmes provides an important tool to understand the cellular phenotypic variation in complex tissues and their response to endogenous and environmental stimuli. While single-cell transcriptomes of several plant organs have been elucidated, the underlying chromatin landscapes associated with cell type-specific gene expression remain largely unexplored.
Gesehen am 08.11.2023